AN EMPIRICAL ANALYSIS OF MERGERS: EFFICIENCY GAINS AND IMPACT ON CONSUMER PRICES. (28th March 2020) - Bonnet, Céline; Philip Schain, Jan
Abstract: In this article, we extend the literature on merger simulation models by incorporating its potential synergy gains into structural econometric analysis. We present an integrated approach. We estimate a structural demand and supply model dealing with two-part tariff contracts between manufacturers and retailers as in Bonnet and Dubois (2010). This model allows us to recover the marginal cost of each differentiated product. Then we estimate potential efficiency gains using the data envelopment analysis approach of Bogetoft and Wang (2005), and some assumptions about exogenous cost shifters. In the last step, we simulate the new price equilibrium post-merger by taking into account synergy gains, and derive price and welfare effects. We use a home scan data set of dairy dessert purchases in France, and show that synergy gains could offset the upward pressure on prices post. Moreover, in this market, the increase in industry profit due to the merger is more driven by its induced synergy gains than by the market power increase.